Sudden death due to acute hemorrhagic necrotizing pancreatitis - Karthi Vignesh Raj, K; Ashok Chaudhari , Vinod; Gochchait, Debasis; Devan , Meyyappa (Journal of Indian Academy of Forensic Medicine, 2019)
It is a great challenge for a forensic pathologist to solve a case of sudden and unexpected death. World Health Organization (WHO) defines sudden death as “death occurring less than 24 hours from onset of symptoms, not otherwise explained”. It is also defined as death known not to be violent or instantaneous for which no cause can be discovered and death without a sign of disease. Sudden death involving the pancreas remains a rare and unusual condition. The reason behind the sudden unexpected death due to pancreatitis is the rapid progress of the condition. Amost common symptom in acute pancreatitis is abdomen pain and vomiting. Alcohol consumption affects the pancreas by direct injury to the acinar cells, ductal obstruction and also hampers the intracellular transport finally landing up in acute pancreatitis. We report a case of acute hemorrhagic necrotizing pancreatitis in a middle-aged male due to chronic alcoholism, substantiated by the histopathology findings, and positive blood alcohol levels. A thorough evaluation of history along with a meticulous autopsy is helpful in finding the etiology of sudden death, especially in the middle-aged adult population. This case highlights the forensic expert’s anticipation with reference to sudden death due to inflammatory pathology.